2022
DOI: 10.1149/10701.11199ecst
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology Goes to School: Conceptualizing Students’ Happiness in 21st Century Schools While ‘Minding the Mind!’ Are We There Yet? Evidence-Backed, School-Based Positive Psychology Interventions

Abstract: The purpose of this article is to examine school-based interventions that have been designed and developed to promote students’ happiness, well-being, and academic achievement using a positive psychology approach that focuses on cultivating positive emotions, resilience, and positive character strengths. The current paper outlines the positive psychology movement and reviews evidence from 12 school-based positive psychology interventions that have been systematically evaluated, in response to calls from the 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 66 publications
2
6
0
1
Order By: Relevance
“…Both interventions displayed significant improvement in comparison with the control group in all variables, i.e., an increase in well-being, gratitude, nature in self, sense of connectedness, resilience, awareness, positive affect, and a decrease in stress and negative affect levels. This is in line with previous meta-analytic evidence on the effectiveness of MBIs in nature ( 34 ), MBIs in schools ( 28 32 ), and PPIs in a school setting ( 36 , 37 ). These findings further add to the studies that we built upon, such as Pirchio et al ( 88 ), who demonstrated positive outcomes of a school intervention focusing on contact with nature (on psycho-physical well-being, connectedness to nature, and prosocial behavior of students) in the intervention group than the control group as well as Choe and Sheffield ( 33 ), offering essential insights on the impact of natural surroundings in improving intervention efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both interventions displayed significant improvement in comparison with the control group in all variables, i.e., an increase in well-being, gratitude, nature in self, sense of connectedness, resilience, awareness, positive affect, and a decrease in stress and negative affect levels. This is in line with previous meta-analytic evidence on the effectiveness of MBIs in nature ( 34 ), MBIs in schools ( 28 32 ), and PPIs in a school setting ( 36 , 37 ). These findings further add to the studies that we built upon, such as Pirchio et al ( 88 ), who demonstrated positive outcomes of a school intervention focusing on contact with nature (on psycho-physical well-being, connectedness to nature, and prosocial behavior of students) in the intervention group than the control group as well as Choe and Sheffield ( 33 ), offering essential insights on the impact of natural surroundings in improving intervention efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, PPIs conducted in a school setting, focusing on positive emotions and positive behaviors, have also received ample support from the literature ( 36 , 37 ) while having the scope for further investigation in India ( 38 ). This is especially relevant for the Indian context: 39% of the Indian population consists of children and youth, often regarded as the nation’s future ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that a positive scholarly climate is related to students' less aggressive behavior [24]. A systematic review of positive psychology interventions in schools concludes that evidence has demonstrated that positive programs are associated with students' health and academic success [25].…”
Section: School As a Positive Institutionmentioning
confidence: 99%
“…Rendahnya tingkat kebahagiaan dapat menurunkan prestasi dan motivasi belajar mahasiswa baru (Alam, 2022). Kebahagiaan yang rendah juga akan menurunkan optimisme mahasiswa baru dalam menjalani kehidupan (Demirtas, 2020).…”
Section: Pendahuluanunclassified